Résistance des corpus longs et déplacements de la recherche: l’exemple de la rédaction conversationnelle - De Gaulmyn, Marie-Madeleine (Studia Romanica Posnaniensia, 2007)
In this article the author presents an analysis of empirical material which consists of a recording of interaction between two female students as they edit together a written text on the subject given them. Various characteristics of these students (nationality, social status, upbringing, their past school experiences) cause conflicts which have not been predicted by the researcher and which influence the final form of the text being edited.